Adherence to oral HIV pre-exposure prophylaxis among female sex workers in Kampala, Uganda - Kakoola Nalukwago, Grace; Isunju, John Bosco; Muwonge, Timothy; Katairo, Thomas; Bunani, Nelson; Semitala, Fred; Kyambadde, Peter; Matovu, Flavia (African Health Sciences, 2021)
In Kampala Uganda, female sex workers (FSWs) have high HIV prevalence (33%). Oral PrEP is a novel HIV prevention intervention that offers hope to decrease HIV incidence in key populations especially among FSWs. Studies have shown that with poor adherence, oral PrEP has no efficacy, and therefore adherence to PrEP is critical among FSWs to maximize HIV prevention. However, implementation data on adherence to PrEP among FSWs is limited so this study sought to assess adherence to PrEP. Specifically, we sought to 1) determine the level of adherence to PrEP among FSWs, and 2) determine factors associated with PrEP adherence. Methods: This cross-sectional study was conducted from November to December 2018; 126 FSWs using PrEP were interviewed using a questionnaire. Adherence was categorically defined as high adherence and low adherence. Logistic regression was done. Results: Using long-term contraception methods (OR 0.06, 95% CI: 0.04-0.77) and not using condoms with clients (OR 0.07, 95% CI: 0.01-0.42) were negatively associated with high PrEP adherence. Conclusion: Barriers to PrEP adherence need to be addressed for successful PrEP implementation to improve adherence going forward. Service care providers should reinforce positive behaviors such as use of condoms devotedly during PrEP breaks.
Keywords: Oral PrEP; Adherence; Female sex workers